The correlation between iodine and metabolism: a review - Zhang, Le; Shang, Fangjian; Liu, Cong; Zhai, Xiaodan (Frontiers in Nutrition, 2024)
Iodine is involved in the synthesis of thyroid hormones and plays a crucial role in human life. Both iodine deficiency and excess are common issues in certain populations.Iodine also has extrathyroidal effects on organs that can uptake it independently of thyroid hormones. Recently, multiple clinical studies have shown a connection between iodine intake and metabolic disorders, such as metabolic syndrome, obesity, diabetes, hypertension, and dyslipidemia. However, the results of these studies have been inconsistent, and the mechanisms behind these associations are still not well understood. Therefore, in this review, we aim to examine the recent research progress regarding the relationship between iodine and metabolic disorders, along with the relevant mechanisms.